Bangladesh-Myanmar Maritime Boundary Delimitation in the Bay of Bengal: An Analysis on the Development of International Law - Hasan Arif, Md. Kamrul (Kathmandu School of Law Review, 2018)
The judgment delivered by the International Tribunal for the Law of the Sea (ITLOS) in the dispute concerning the delimitation of the maritime boundary between Bangladesh-Myanmar in the Bay of Bengal has a historic significance. The Bay of Bengal is an important area for many significant reasons for both the parties. To explore and for the exploitation of living and non-living resources, this judgment has played a vital role. The unique contribution of the judgment is that, the extension of the continental shelf beyond 200 nautical miles (nm) from the baseline, and pronouncement of the grey area. This article mainly focuses on the contribution of the case in international law which covers: background of the dispute; straight baseline; continental shelf beyond 200 nm; the role of the Commission on the Limits of the Continental Shelf (CLCS) to delimit the continental shelf beyond 200 nm; and the grey area. Before the conclusion. It also focuses on the theory of natural prolongation and the dissenting opinion given by the judge of the Tribunal. DOI: https://doi.org/10.46985/jms.v6i2.210